Analysis of serum lysophosphatidylethanolamine levels in patients with non-alcoholic fatty liver disease by liquid chromatography-tandem mass spectrometry - Yamamoto, Yusuke; Sakurai, Toshihiro; Chen, Zhen; Furukawa, Takayuki; Gowda, Siddabasave Gowda B.; Wu, Yue; Nouso, Kazuhiro; Fujii, Yuki; Yoshikawa, Yuki; Chiba, Hitoshi; Hui, Shu-Ping (Analytical and bioanalytical chemistry, 2021)
Lysophosphatidylethanolamines (LysoPEs) are the partial hydrolysis products of phosphatidylethanolamine. Despite the unique in vitro bioactivities of LysoPEs, there are limited reports on the pathophysiological role of LysoPEs in the serum, due to the lack of sensitive analytical methods for determination of each molecular species in clinical samples. Herein, we developed a highly sensitive quantitative method to profile the serum LysoPE species by liquid chromatography-tandem mass spectrometry (LC-MS/MS) with selected reaction monitoring (SRM). The internal standard (IS), chemically synthesized in-house, and the lineup of seven major LysoPE species were used in this study. The limits of detection and quantification for each LysoPE species ranged within 0.5–3.3 pmol/mL and 1.0–5.0 pmol/mL, respectively. The combined concentrations of LysoPEs in the serum from healthy subjects ( n = 8) and the patients with non-alcoholic fatty liver diseases (NAFLD) including simple steatosis (SS, n = 9) and non-alcoholic steatohepatitis (NASH, n = 27) were 18.030 ± 3.832, 4.867 ± 1.852, and 5.497 ± 2.495 nmol/mL, respectively. The combined and individual concentrations of LysoPEs, except for LysoPE 18:0, significantly decreased in the patients with NAFLD compared with those for the healthy subjects. However, no significant difference was observed between the SS and NASH groups. Our proposed LC-MS/MS method is valid and has advantages of small sample volume, high sensitivity, and simultaneous absolute quantitation for multiple molecular species. This method may enable diagnostic evaluation and elucidation of the as-yet uncovered pathophysiological role of LysoPEs. Graphical abstract